Indigenous education in Russia: opportunities for healing and revival of the Mari and Karelian Indigenous groups? - Khanolainen, Daria; Nesterova, Yulia; Semenova, Elena (Taylor and Francis, 2022)
Despite being a multicultural country throughout its history, the Russian Federation has long struggled to embrace its diversity. As a result, the country’s many cultural, religious, and ethnic minority groups have been going through waves of assimilationist policies and practices. Assimilation into the Russian society enforced through formal schooling, daily life, and mass media has led to a destruction of Indigenous lifestyles, cultures, identities, and languages. This article explores the views of Russia’s Indigenous people regarding the country’s education system and its ability to support the cultural revival of Indigenous groups as well as the healing of the trauma that emerged from historical oppression. Within the scope of this article, we investigate the views of two Indigenous groups: Mari and Karelian peoples. Their insights show that despite the decrease in discrimination, the education system has not yet changed its assimilative tendencies.